A new approach to estimate transaction costs: an empirical evidence - Abdullah, Mimi Hafizah (2012)
This study offers an innovative way as an alternative to estimate the total transaction costs in stock trading via the implied transaction costs by using the Leland option pricing model. The effectiveness of this new approach is tested by using the S&P/ASX 200 index call options data. Based on the actual transaction costs estimates on the Australian Securities Exchange (ASX) documented by previous studies and the Roll’s model, the empirical results reveal that this new approach can provide a reliable transaction costs estimate on stock trading in the ASX. Furthermore, the accuracy of the implied transaction costs across option moneyness and maturity is investigated.